PENGEMBANGAN MEDIA PEMBELAJARAN FILM PENDEK SUB MATERI KEDATANGAN BANGSA-BANGSA BARAT KE-INDONESIA - Fiki, Ahmad; Sujono, Imam; S, I Sukwatus (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Thisistudy aimsito find out: 1) Steps to develop short film learning media on the arrival of westerners to Indonesia, 2) the validity of using short film learning media on the arrival of westerners to Indonesia for class VIII MTs students. This research uses the research and development method or Research and Development which refers to the Borg and Gall model. The research subjects were 25 students of class VIII A at MTs Aswaa Tunggangri. The data collection technique was in the form of a validation questionnaire for media experts, material and social studies teachers. The validity of using short film learning media, namely the first media validation produced 78.66%, material 82.66%, social studies teachers 82.66% and all of them are valid categories. Student response questionnaires yielded 86.3%, pre-test scores from the control class amounted to 57.5% and the experimental class amounted to 73%. Furthermore, the results of the Post-test, found an increase in student learning outcomes. the class value of the control group was 70.41% and in the experimental group was 85.46%, it can be concluded that the development of short film media is stated to be valid and feasible.